Memperbaiki Kinerja Mutu dengan Menggunakan Metode FMEA pada Industri Karung Tenun Polypropylene - Fatah, Kemas Muhammat Abdul; Wisnaningsih, Wisnaningsih (Proceeding Mercu Buana Conference on Industrial Engineering, 2023)
The quality failure rate in the production process in the form of defective products, scrap products, rework, rejection, and waste is an indicator of a company's quality performance, especially with regard to cost quality.  Failure in the production process will increase the rate of defects, scrap, rework, rejection, and waste, which in turn will increase the cost of quality. This study uses the FMEA method to fight identified failures from gemba walk activities. Improvements made using the FMEA method with several recommendations for improvement solutions can reduce failures, this can be seen by comparing the RPN values. The RPN failure value in the extrusion process which affected the hollow or loose PP woven sacks decreased to 98 from 490, and which resulted in lighter sack weight decreased to 98 from 490. The decrease occurred due to the achievement of the process capability value (Cpk) which was as expected ie 1.36 for denier specifications and 1.33 for yarn bandwidth specifications. This Cpk achievement has an impact on a decrease of the occurrence (o) level. Meanwhile, the failure of the RPN value in the weaving process which had an impact on products returned by customers, decreased to 98 from 490. The decrease occurred because the weaving process operator was given the responsibility to carry out maintenance and cleanliness of the machine which resulted in a decrease of the occurrence (o) level.